Attention and Blood Lactate Levels in Equestrians Performing Show Jumping. Issue 3 (June 2014) - Perciavalle, Valentina; Di Corrado, Donatella; Scuto, Claudia; Perciavalle, Vincenzo; Coco, Marinella
In equestrian show jumping, attention is particularly important to ensure maximum accuracy. Due to the anaerobic nature of the jumping and its requirement for precision coordination between human and horse, there may be a relation between the onset of lactic threshold and decrease in attention. In 12 healthy and injury-free equestrians (6 men, 6 women), the effects (blood lactate and glucose) of a show jumping course (250 m long with eight vertical obstacles with a height of 1.15 m height) on capacity and selectivity of attention was assessed. A typical reaction time paradigm and test of divided attention were administered. At the end of the course a significant increase of blood lactate was observed, whereas blood glucose did not significantly change. A deterioration of attention (intensity and selectivity) and a worsening of performance with increasing of blood lactate were observed. The present results led to the conclusion that the increase in blood lactate that occurs in riders executing a show jumping course is associated with worsening of both attentive capabilities and performance.